Case Report: Adenylosuccinate lyase deficiency type I caused by splicing disruption due to a novel missense variant in the ADSL gene - Borovikov, Artem; Davydenko, Ksenia; Murtazina, Aysylu; Sharkov, Artem; Kanivets, Ilya; Filatova, Alexandra; Skoblov, Mikhail (Frontiers in Genetics, 2025)
Adenylosuccinate lyase deficiency (ALD) is a rare neurometabolic disorder caused by biallelic loss-of-function variants in the ADSL gene. We report a severe type I ALD case involving a 2-year-old boy presenting with early-onset polymorphic seizures (clonic/myoclonic), developmental delay, and progressive neurological deterioration. Seizures were temporarily controlled with ethosuximide and vigabatrin, though neurodegeneration progressed. Analysis of whole-exome sequencing data revealed compound-heterozygous variants in the ADSL gene: the known pathogenic missense variant c.340T>C (p.Tyr114His) and a novel variant c.859A>G (p.Ile287Val). Although p.Ile287Val is predicted to be benign at the protein level, RNA analysis demonstrated that c.859A>G activates a cryptic splice site in exon 8, resulting in aberrant transcripts (64%, 4-bp deletion, targeted by nonsense-mediated decay) and a smaller proportion of normal transcripts (36%) encoding the p.Ile287Val protein. This case highlights splicing disruption as a novel pathogenic mechanism in ALD and expands the mutational spectrum associated with the disease. This case also underscores the importance of integrating RNA analysis with genomic data to uncover cryptic splicing defects, especially when protein-level predictions suggest benignity.